2019
DOI: 10.1186/s13023-019-1047-z
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of classic galactosemia: lessons from the GalNet registry

Abstract: Background Classic galactosemia is a rare inborn error of carbohydrate metabolism, caused by a severe deficiency of the enzyme galactose-1-phosphate uridylyltransferase (GALT). A galactose-restricted diet has proven to be very effective to treat the neonatal life-threatening manifestations and has been the cornerstone of treatment for this severe disease. However, burdensome complications occur despite a lifelong diet. For rare diseases, a patient disease specific registry is fundamental to monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
155
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(171 citation statements)
references
References 49 publications
7
155
1
8
Order By: Relevance
“…The Galactosaemia Consortium (GalNet) Registry outcome study [9] has recently demonstrated that 80% of females (of n = 164) have primary ovarian insufficiency which is consistent with other studies [4,5,6,7,8,26,27].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…The Galactosaemia Consortium (GalNet) Registry outcome study [9] has recently demonstrated that 80% of females (of n = 164) have primary ovarian insufficiency which is consistent with other studies [4,5,6,7,8,26,27].…”
Section: Introductionsupporting
confidence: 79%
“…Restriction of galactose is life-saving in the neonate and improves the neonatal intoxication manifestations of feeding difficulties, failure to thrive, sepsis, hepatocellular damage, renal tubulopathy, and cataracts. Affected individuals develop long term complications affecting the central nervous system, bone density/metabolism, and primary ovarian insufficiency and subfertility in females despite dietary galactose restriction [4,5,6,7,8,9]. Primary ovarian insufficiency in CG, first described in 1978 [10] with ovarian follicular depletion is reported in at least 80% of females [9].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, the incidence of CG is estimated to be 1:52 800 in the Netherlands ( Welling et al , 2017 b ). Despite an early diagnosis by NBS and treatment with a galactose-restricted diet, patients are at risk to develop long-term complications of the central nervous system, such as abnormalities in motor and speech development, cognitive impairment and movement disorders (MDs) and ovarian insufficiency in females ( Bosch, 2006 ; Hughes et al , 2009 ; Waisbren et al , 2012 ; Coss et al , 2013 ; Rubio-Gozalbo et al , 2019 ). There is a broad spectrum of clinical manifestations ranging from fully normal to severely impaired, even within families with identical mutations ( Fridovich-Keil and Walter, 2008 ; Hughes et al , 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The international network for the galactosemias (GalNet), established in 2012, has developed an online registry (https:// ecrf.ctcm.nl/macro/) that includes patients with the different galactosemias from several countries as described in Rubio-Gozalbo et al 19 It was established in accordance with Good Clinical Practice and following General Data Protection Regulation. The local ethics committee of the coordinating center (Maastricht University Medical Center) approved the study (application number METC 13-4-121.6/ab), which was subsequently approved by participating partners.…”
Section: Ethics Statementmentioning
confidence: 99%